An Instructional Design For The Teaching Of Writing At Eight Grade Of SMP Negeri 2 Colomadu In 2013/2014 Academic Year - Alam, Rosa Rustiana Sabda, Prof. Dr. Endang Fauziati, M. Hum, Aryati Prasetyarini, S.Pd, M.Pd (2014)
The study is aimed at observing the instructional design on teaching writing skill the at eight grade of SMP Negeri 2 Colomadu in 2013/1014 academic year. The objective of study is to describe instructional design in teaching learning process of writing skill at SMP Negeri 2 Colomadu. In this research, there are nine components of instructional design in teaching writing skill that the writer analyze, namely: (1) Learning Objective. (2) The Syllabus. (3) The Instructional Material. (4) The Classroom Procedure. (5) Technique in Teaching Writing. (6) Teacher's Role. (7) Learner's Role. (8) Evaluation Model and (9) Teaching Media. The type of the study is descriptive qualitative especially naturalistic approach. In this research, the data are taken from event and informant. There are three techniques of collecting data, namely: observation, interview, and document. The techniques of analyzing data are reduction of data, display the data, and verification or drawing conclusion. The results of the study, show that: (1) There are two learning objectives of teaching English especially in writing skill namely: general objective and specific objective. In general learning objective is to develop communicative competence in spoken and written form to deal with the development of science and technology in facing the globalization era. In specific learning objective is written in indicator of lesson as follows: identifying many kinds of recount text, answering the question of recount text, completing blank text of recount, arranging word or sentence become a recount text, writing a simple recount text based on situation. (2) The type of syllabus is notion functional syllabus. (3) The instructional material used is printed material and the material that compare both print and non print source as sell access material and material on the internet. (4) the classroom procedure used is 5E (Engagement, Exploration, Explanation, Elaboration and Evaluation) with different patterns. (5) Techniques used in teaching writing skill are brainstorming, instructor-initiated question and probes, discussion a topic or question, peer-editing and the instructor's feedback. (6) The teacher's roles are facilitator, classroom manager, instructor, consultant, and evaluator. (7) The learner's role are monitor and evaluation their progress, learner learn from the teacher, members of a group and learn by interacting with others. (8) Evaluation model applied are daily examination, middle text and final test and the evaluation comprises are completing a paragraph, making a sentence etc. (9) The media used in teaching learning process are textbook as printed media and LCD projector as electric media.